Rekonstruksi Disiplin Siswa Implementasi Pengkondisian Operan dalam Membentuk Budaya Belajar yang Responsif - Rahma Pramudiana Pratama; M. Mamduh Winangun (JURNAL ILMIAH NUSANTARA, 2026)
When B.F. Skinner successfully demonstrated that human behavior is entirely determined by its consequences, the world of education should have received a strong scientific signal to make fundamental changes. Unfortunately, more than 70 years since the theory of operant conditioning was formally formulated, classrooms around the world, including in Indonesia, still rely on outdated disciplinary approaches that emphasize fear rather than genuine character development. This is the most striking discrepancy in modern education: we possess the knowledge, but rarely apply it. This research emerges as a step toward a paradigm shift in viewing school discipline, using Burrhus Frederic Skinner's theory of operant conditioning as its primary foundation. Through mechanisms such as positive reinforcement, negative reinforcement, punishment, and extinction, this theory provides practical scientific guidance for teachers to purposefully shape, strengthen, and modify student behavior. This study aims to conduct an in-depth analysis of how these principles can be applied contextually and responsibly in daily teaching and learning routines, in order to create an adaptive learning culture—that is, an environment where students are not merely robotically obedient, but fully engaged, responsible, and intrinsically motivated.